(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The relevance of this research is based on the implications of low financial autonomy of rural municipalities referred to by the researchers, economists, and policymakers. The phenomenon of financial autonomy of municipalities is widely declared in the legal documents of the European Union (EU), analysed by the researchers comprehensively, including identification of the issues and proposal of the solutions Nonetheless, it is not ensured sufficiently in practice. EU’s Common Agricultural Policy emphasizes the importance of rural development on the development of country’s regions, and researchers emphasize the direct impact of the fiscal policy measures applied by the country on the financial autonomy of the local governments. The research aims to assess the impact of fiscal policy measures on the financial autonomy of rural municipalities in Lithuania. The research findings have revealed the dependence of the local governments on the central government, which is indicative of the poor possibilities for the rural municipalities to redistribute funds at own discretion and form the regional policy. The research has identified the fiscal measures determining the poor financial autonomy of the rural municipalities in Lithuania as well as the reasons behind the difference between the municipalities. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.